Improving Type 2 Diabetes Patient Health Outcomes with Individualized Continuing Medical Education for Primary Care. Issue 3 (September 2016) - Lee, Brian; Trence, Dace; Inzucchi, Silvio; Lin, Jay; Haimowitz, Steven; Wilkerson, Elizabeth; Williams, Cara; Mosier, Marc; Dex, Terry
Abstract Introduction This study provided physicians with continuing medical education (CME) related to type 2 diabetes and evaluated the effect on patient health outcomes. Methods Physicians participated in multi-platform CME (live and online programs) and completed a 25 item questionnaire for patient baseline (3-months pre-CME activity) and follow-up visits (≥6-months post-CME activity). Changes in physician knowledge and patient health outcomes were evaluated. Results 34 physicians completed both phases of the CME curricula and submitted data for 264 patients. Significant improvements were observed in physician knowledge after the live (p  < 0.05) and online programs (p  < 0.0005). Mean patient glycated hemoglobin (HbA1c) absolute reduction of 1.15% (p  < 0.0001) was reported. Conclusions CME is an effective tool to close established practice gaps and potentially help improve patient health outcomes.